The Politics of Faith and Force: A Micro-Foundational Analysis of the transformation of Hefazat-e-Islam Bangladesh - Md. Al-Amin; Md. Sunbin Islam; Sushmita Roy (Asian Studies, 2025)
The research goes through the heart of Hefazat-e-Islam’s (HI) transformation from a non-violent religious movement to an agent of political violence, highlighting how its leadership strategically harnesses emotionally charged religious discourse to mobilize support and gradually escalate ostensibly peaceful activism into violent confrontation. The study finds that while HI initially emerged as a non-violent religious movement, its leadership gradually utilized evocative religious rhetoric and symbolic frameworks to mobilize followers. This strategic use of religious discourse transformed ostensibly peaceful activism into potential flashpoints of escalation, where participants—whether intentionally or not—began to prioritize rigid religious or ultranationalist identities over-inclusive or pluralistic values, shaping their decision-making within the movement. In this process, HI propagated narratives opposing Bengali cultural ideology, promoting anti-secular sentiments, communal agendas, and portraying sculptures as idolatrous rather than artistic expressions. These ideas were disseminated through a range of mechanisms, including sermons, social media, da’wa, manhaji, and the Qawmi madrasa network. Consequently, followers, often consciously or unconsciously aligned with HI’s messaging, mobilized en masse to demonstrate strength, ultimately contributing to the rise of religiously motivated extremism and political violence.